Mengungkap Misteri Angka: Jejak Keterkaitan Antara Matematika Dan Angka Dalam Bahasa Arab (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Nurul Hakim, 2023)
This study aims to conduct a detailed analysis of the close relationship between Arabic and the evolution of the concept of numbers in the history of mathematics. Using a literature research approach, this study investigates the historical traces of the Arabic numeral system, especially in the context of the emergence of mathematical numerals and numerals in Arabic. In addition, this study explores the impact of the interrelationship between mathematics and Arabic on the development of science, as well as how this influence extends across cultural and linguistic boundaries. The results reveal that the course of the history of the Arabic numeral system provides a deep understanding of the key role of this language in changing the way we understand and apply mathematical concepts.